Values in the media discourse on COVID-19 - Polkowska, Laura (Papers in Linguistics, 2022)
The text constitutes an attempt to reconstruct values referred to in the media discourse on COVID-19. The research covered four Internet portals (wyborcza.pl, onet.pl, wpolityce.pl and niezalezna.pl) and two periods (the end of March 2020 and the end of February 2021). An automatic quantitative analysis of the text corpora created for the purpose of the study was extended to include a detailed contextual analysis. As a result, eight frequency lists were created, containing the most commonly used names referring to values. i.e. axiological lexemes. They are presented in detail later in the article. Particular attention was paid to the specific discursive profiling of some axiological lexemes and to fixed phrases that contain references to values.